2014
DOI: 10.7748/ns.28.45.37.e8661
|View full text |Cite
|
Sign up to set email alerts
|

Using abdominal massage in bowel management

Abstract: This article describes the introduction of abdominal massage techniques by a community team as part of a total bowel management programme for people with learning disabilities. A trust-wide audit of prescribed laxative use by this client group raised concerns, and led to a more systematic approach to managing constipation in people with learning disabilities. An education programme for carers proved to be successful. Some reported that adopting abdominal massage provided further opportunity to develop the ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 0 publications
0
23
0
9
Order By: Relevance
“…The type of laxatives used by participants is outlined in seven quantitative descriptive studies (Böhmer, Taminiau, Klinkenberg‐Knol, & Meuwissen, ; Connor, Hunt, Lindley, & Adams, ; Ganesh, Potter, & Fraser, ; van der Heide et al., ; Joos, Mehuys, Remon, Van Winckel, & Boussery, ; Van Winckel et al., ; Veugelers et al., ). The highest quality study found that the most commonly used laxatives in children with severe generalized cerebral palsy mostly living in the family home were disaccharide (24.3% of 152 children) and polyethylene glycol (macrogol) (13.2% of 152 children) (Veugelers et al., ).…”
Section: Laxative Typesmentioning
confidence: 99%
See 4 more Smart Citations
“…The type of laxatives used by participants is outlined in seven quantitative descriptive studies (Böhmer, Taminiau, Klinkenberg‐Knol, & Meuwissen, ; Connor, Hunt, Lindley, & Adams, ; Ganesh, Potter, & Fraser, ; van der Heide et al., ; Joos, Mehuys, Remon, Van Winckel, & Boussery, ; Van Winckel et al., ; Veugelers et al., ). The highest quality study found that the most commonly used laxatives in children with severe generalized cerebral palsy mostly living in the family home were disaccharide (24.3% of 152 children) and polyethylene glycol (macrogol) (13.2% of 152 children) (Veugelers et al., ).…”
Section: Laxative Typesmentioning
confidence: 99%
“…Macrogol combinations were also the most frequently prescribed laxative for adults and children with profound intellectual and multiple disabilities (PIMD) living in institutions in the Netherlands (30% of 254 people with PIMD) followed by bisacodyl (29%) and lactulose (14%) (van der Heide et al., ). An earlier study in England found only four of 181 people living in community‐based care homes (2.2%) to be taking macrogol, with the most frequent being lactulose (46 of 181; 25.4%) and senna (27 of 181; 14.9%) (Connor et al., ).…”
Section: Laxative Typesmentioning
confidence: 99%
See 3 more Smart Citations